2005
DOI: 10.1590/s0102-695x2005000400007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, agronomical and pharmacological characterization of Hyptis pectinata (L.) Poit germplasm

Abstract: Several species of the genus Hyptis have presented medicinal characteristics and are frequently indicated to treat gastro intestinal infections, gramps and pain, as well as for skin infections. Three harvests were carried out using six H. pectinata accessions, and the following characteristics were evaluated: plant height, canopy diameter, leave length (L) and width (W), L/W relation and dry weight of leaves and stem. The accession SAM006 have presented highest leave dry matter yield when the three harvests we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Table 4 shows the p-values for the differences between samples. Chemical polymorphism in the genus Hyptis have been investigated by several authors (Azevedo et al, 2001;Arrigoni-Blank et al, 2005). Results showed that genetic variations within the same species, as well as the climate and soil types, could vary the chemical characteristics of the active constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Table 4 shows the p-values for the differences between samples. Chemical polymorphism in the genus Hyptis have been investigated by several authors (Azevedo et al, 2001;Arrigoni-Blank et al, 2005). Results showed that genetic variations within the same species, as well as the climate and soil types, could vary the chemical characteristics of the active constituents.…”
Section: Resultsmentioning
confidence: 99%
“…Among these species, H. pectinata, popularly known in the Brazilian Northeast as "sambacaitá" or "canudinho", is extensively used in folk medicine in the treatment of bacterial infections and inflammation (ARRIGONI-BLANK et al, 2005). In addition, several biological properties of its essential oils or extracts have already been proved, such as its antidematogenic, antinociceptive , antimicrobial , insecticide (SILVA et al, 2008), anti-inflammatory (RAYMUNDO et al, 2011), and leishmanicide activities (FALCAO et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extract from the H. pectinata leaves was investigated for its antinociceptive and antioedematogenic properties. The extract showed positive results on the abdominal contortions and hot plate analgesy models and antinfl ammatory activity in the paw oedema model (Bispo et al, 2001;Arrigoni-Blank et al, 2005;Falcão et al, 2005). The same laboratory demonstrated that the aqueous extract of H. pectinata accelerated liver regeneration after hepatectomy in rats (Melo et al, 2005).…”
Section: Introductionmentioning
confidence: 92%
“…It is commonly cultivated in the backyards of many Brazilian houses where the plant is used as an analgesic and antiinfl ammatory preparation obtained from its leaves by decoction or infusion. (Carvalho, 1999;Arrigoni-Blank et al, 2005;Falcão et al, 2005). H. pectinata is also described in Brazilian folk medicine for the treatment of rhinopharyngitis, nasal congestion, skin diseases, fever, bacterial and fungi infections (Malam et al, 1988;).…”
Section: Introductionmentioning
confidence: 99%